A Cu-functionalized MOF and multi-walled carbon nanotube composite modified electrode for the simultaneous determination of hydroquinone and catechol. Issue 40 (29th September 2022) - Zhang, Hong-jing; Zou, Xin; Chen, Wen-yi; Sun, Qian; Gao, En-qing
Abstract : A novel electrochemical sensor based on a copper-functionalized MOF composite for simultaneously determining dihydroxybenzene isomers in actual water samples. Abstract : Designing MOF-based materials with desired electrochemical activity and high electron conductivity may yield a novel electrochemical sensor that effectively detects various organic pollutants and conducts health monitoring. This study developed a facile and versatile electrochemical sensor for simultaneously monitoring the environmental pollutants hydroquinone (HQ) and catechol (CT). The electrodes are fabricated by modifying a GCE with a Cu-functionalized MOF (UiO-bpydc-Cu) and multi-walled carbon nanotubes (MWCNTs). The Cu-functionalized MOF effectively improved the electronic conductivity by metalating the 2, 2′-bipyridyl-derived UiO-bpydc with Cu 2+ ions. Moreover, due to the synergic effect, the composite electrode exhibits a significant voltammetric response to HQ's and CT's electro-redox. A rapid and sensitive method of synchronously detecting HQ and CT has been established by differential pulse voltammetry (DPV). The experiments reveal that the linear response ranges were 0.5–565 μM and 1–1350 μM for HQ and CT, respectively, with low detection limits of 0.361 μM and 0.245 μM. The proposed UiO-bpydc-Cu/MWCNTs/GCE electrochemical sensor shows high sensitivity, good anti-interference, reproducibility, and stability. It can also be applied for detecting HQ and CT in actual samples.